HOW TO FOSTER GREEN ENTREPRENEURIAL INTENTION - Axel Anabel Tangguh; Kartika Nuringsih (Graduate Program of Universitas Tarumanagara, 2026)
As an alignment with sustainable development goals (SDGs), the agenda is introduced in entrepreneurship learning through green entrepreneurship. Therefore, the purpose of this study is to explore the factors that influence green entrepreneurial intention based on green entrepreneurial orientation, green economy perception, and green entrepreneurship education. This study emphasizes on students' perception in understanding the green concept. Respondents consisted of 153 students at the Faculty of Economics and Business, Tarumanagara University Jakarta, Indonesia. The sample selection technique uses purposive sampling with the criteria that students have received SDG learning. The results of structural regression analysis show that green economic perceptions and green entrepreneurship education have a positive and significant influence on green entrepreneurial intentions while green entrepreneurial orientation has no effect. The result is as information for universities in creating curriculum innovations to increase experience, skills, and insight to students about being proactive in dealing with uncertainty in the green business era. Collaboration with stakeholders to realize a SDG-oriented curriculum to form a green entrepreneurial orientation. This approach can encourage innovation, proactivity, and risk-taking in line with green business, therefore contributing to the ranking and reputation of environmentally-oriented university management.